EP240801a/XRF 240801B: An X-Ray Flash Detected by the Einstein Probe and the Implications of Its Multiband Afterglow - Shuai-Qing Jiang; Dong Xu; Agnes P. C. van Hoof; Wei-Hua Lei; Yuan Liu; Hao Zhou; Yong Chen; Shao-Yu Fu; Jun Yang; Xing Liu; Zi-Pei Zhu; Alexei V. Filippenko; et al. (The Astrophysical Journal Letters)
We present multiband observations and analysis of EP240801a, a low-energy, extremely soft gamma-ray burst (GRB) discovered on 2024 August 1 by the Einstein Probe (EP) satellite with a weak contemporaneous signal also detected by the Fermi Gamma-ray Burst Monitor (GBM). Optical spectroscopy of the afterglow, obtained by Gran Telescopio Canarias and Keck, identified the redshift of z = 1.6734. EP240801a exhibits a burst duration of 148 s in X-rays and 22.3 s in gamma rays, with X-rays leading by 80.61 s. Spectral lag analysis indicates that the gamma-ray signal arrived 8.3 s earlier than the X-rays. Joint spectral fitting of EP Wide-field X-ray Telescope and Fermi/GBM data yields an isotropic energy ${E}_{γ ,{\rm{iso}}}=(5.5{7}_{-0.50}^{+0.54})× 1{0}^{51}\,{\rm{erg}}$ , a peak energy ${E}_{{\rm{peak}}}=14.9{0}_{-4.71}^{+7.08}\,{\rm{keV}}$ , and a fluence ratio S (25–50 keV)/ S $(50\,\unicode{x02013}\,100\,{\rm{keV}})=1.6{7}_{-0.46}^{+0.74}$ , classifying EP240801a as an X-ray flash (XRF). The host-galaxy continuum spectrum, inferred using Prospector , was used to correct its contribution for the observed outburst optical data. Unusual early R -band behavior and EP Follow-up X-ray Telescope observations suggest multiple components in the afterglow. Three models are considered: a two-component jet model, a forward-reverse shock model, and a forward shock model with energy injection. All three provide reasonable explanations. The two-component jet model and the energy injection model imply a relatively small initial energy and velocity of the jet in the line of sight, while the forward-reverse shock model remains typical. Under the two-component jet model, EP240801a may resemble GRB 221009A (BOAT) if the bright narrow beam is viewed on-axis. Therefore, EP240801a can be interpreted as an off-beam (narrow) jet or an intrinsically weak GRB jet. Our findings provide crucial clues for uncovering the origin of XRFs.